Nebivolol prevents indomethacin-induced gastric ulcer in rats. (3rd July 2016) - El-Ashmawy, Nahla E.; Khedr, Eman G.; El-Bahrawy, Hoda A.; Selim, Hend M.
Abstract: Gastric ulcer is a very common gastrointestinal disease that may lead to dangerous complications and even death. This study was conducted to evaluate the prophylactic effect of nebivolol against indomethacin [INDO]-induced gastric ulcer. Male Wistar rats were divided into four groups: normal control, ulcer control (INDO only), omeprazole before INDO and nebivolol before INDO. Each rat to receive nebivolol and omeprazole was given the agent orally (by gavage) daily for 10 days prior to induction of ulcer by oral dosing with INDO. Four hours after INDO treatment, all rats were euthanized and their stomachs obtained for measures of gastric acidity, oxidative stress and inflammatory markers, as well as cytoprotective mediators. The results showed that a single oral dose of INDO (100 mg/kg) induced gastric acidity, an ulcer index of 2900 and significantly increased levels of gastric tumor necrosis factor (TNF)- α and malondialdehyde (MDA) and significantly decreased levels of gastric prostaglandin E2 (PGE2 ), glutathione (GSH) and nitric oxide (NO), compared to in normal control counterpart stomachs. Giving nebivolol before INDO corrected the gastric acidity and resulted in a significant increase in GSH, PGE2 and NO and a significant decrease in TNF α and MDA gastric levels, compared to ulcer control values. Results obtained with nebivolol were comparable to those with omeprazole; the preventive index in the nebivolol group was 90.7% compared to 94.5% in rats in the omeprazole group. These studies showed that nebivolol provided a valuable role in preventing gastric ulcers induced by INDO and provided a promise for potentially protecting hypertensive patients from experiencing gastric ulcer. Thus, it is possible that, pending further studies, nebivolol could be used for pre-exposure prophylaxis from gastric ulcer in these patients.